CURRICULUM IMPLEMENTATION STRATEGIES AT THE JUNIOR SECONDARY SCHOOL: SOCIAL STUDIES PERSPECTIVES - UZOKIFE, Georgina Chinelo,; OBAJE, Alex Friday PhD, (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
Development of curriculum is one of the major debates in the developing countries with particular reference to Nigeria but the detail of how the curriculum will be implemented at school level are often neglected. This paper examined curriculum implementation strategies at the junior secondary school level. The study adopted a descriptive survey design which focused on investigating curriculum implementation strategies at the junior secondary school. The target population for the study comprised all the junior secondary schools in Ankpa Local Government Area, Kogi State and the sample for the study consisted of 120 junior secondary school teachers drawn using purposive sampling technique from the selected junior secondary schools in Ankpa Local Government Area, Kogi State. Researchers’ constructed questionnaire titled Curriculum Implementation Strategies at the Junior Secondary School Questionnaire (CISJSSQ) was used to measure teachers’ opinion on curriculum implementation strategies at the junior secondary school. The instrument has 15 items on a four-point Likert-scale of strongly agree (SA), Agree (A), Disagree (D) and strongly disagree (SD). This instrument was validated by three experts in the departments of Social Science Education, and Educational Psychology, Guidance and Counselling Nnamdi Azikiwe University. The researchers distributed and collected the copies of the questionnaire with the help of eight research assistants from the junior secondary schools. The data collected were analyzed using the weighted mean of 2.50 computed as 4+3+2+1=10/4=2.5. Any mean score that is equal to or above 2.50 was considered significant and therefore, accepted while the one that is less than 2.50 was rejected. Findings showed that teachers of social studies are not effective in implementing various curriculum strategies during teaching and learning in junior secondary school, teachers of social studies do not teach appropriate contents in the social studies curriculum during classes and teachers of Social Studies do not employ proper method of teaching social studies and the objectives are not achieved. Based on this, it was recommended that the federal and state ministry of education should encourage the teachers through training and re-training to employ better implementation strategies for social studies curriculum among others.